A rural archaeological approach of the Swahili coast in Kenya : Sango Farm Mtetemo, a medieval site in the Tana Delta - (:unkn) unknown (My University, 2020)
This video is a recorded communication showing the state of my PhD research. This presentation was prepared for the Laboratório de Estudos de Outros Medievos hosted by the Universidade Federal de Pernambuco (Brasil). The video is hosted on Youtube : https://www.youtube.com/watch?v=-JgNYaBT3rQ&t=17s&ab_channel=OutrosMedievosAnd followed by a Q&A interview conducted by Prof. Dr. Otávio Luis Vireira Pinto, professor de História da África da Universidade Federal do Paraná : https://www.youtube.com/watch?v=6Yr08VW1E2M&t=1s&ab_channel=OutrosMedievos
Keywords: African Research